PERAN KESEHATAN KARDIORESPIRATORI DALAM MENINGKATKAN PERFORMA ATLET SEPAK BOLA: TINJAUAN PUSTAKA - Ardiansyah, Anas; Yewen, Oktovianus; Widiyanto, Widiyanto (STKIP Melawi, 2025)
Abstract: Cardiorespiratory fitness plays a crucial role in football performance, influencing endurance, speed, and overall success on the field. This study aimed to explore the impact of cardiorespiratory fitness on football performance through a systematic review and meta-analysis, following the PRISMA protocol. Relevant studies on elite football teams were analyzed to assess the relationship between fitness and performance. The results revealed a strong positive correlation between high cardiorespiratory fitness and improved football performance. Players with superior fitness levels demonstrated better endurance and speed, contributing to their overall on-field success. The study concludes that enhancing cardiorespiratory fitness through targeted training programs can significantly improve players' physical abilities, ultimately boosting the performance of football teams. This emphasizes the importance of incorporating fitness-focused training in football to maximize players' potential and ensure better results in competition.Keywords: Cardiorespiratory Fitness, Effective Training Programs, Football Performance. Abstrak: Kebugaran kardiorespirasi memainkan peran penting dalam performa sepak bola, mempengaruhi daya tahan, kecepatan, dan keberhasilan di lapangan. Studi ini bertujuan untuk menyelidiki dampak kebugaran kardiorespirasi terhadap performa sepak bola melalui pendekatan Tinjauan Sistematis dan Meta-Analisis yang mengikuti protokol PRISMA. Studi-studi yang relevan tentang hubungan kebugaran kardiorespirasi dan performa sepak bola pada tim elit dianalisis untuk menarik kesimpulan yang bermakna. Hasil meta-analisis menunjukkan korelasi positif yang kuat antara tingkat kebugaran kardiorespirasi yang tinggi dengan peningkatan performa sepak bola. Pemain dengan kebugaran yang lebih baik menunjukkan daya tahan, kecepatan, dan performa di lapangan yang lebih tinggi dibandingkan pemain dengan kebugaran rendah. Hasil ini menyimpulkan bahwa peningkatan kebugaran kardiorespirasi melalui program pelatihan yang terarah dapat secara signifikan meningkatkan kemampuan fisik pemain dan berkontribusi pada kesuksesan tim sepak bola.Kata Kunci: Kebugaran Kardiorespirasi, Program Pelatihan yang Efektif, Performa Sepak Bola